A noble silver nanoflower on nitrogen doped carbon nanotube for enhanced oxygen reduction reaction. (12th January 2017) - Yasmin, Sabina; Shamsuddin Ahmed, Mohammad; Jeon, Seungwon
Abstract: An electrodeposition-approach for the synthesis of silver nanoflowers (AgNFs) on nitrogen doped carbon nanotubes (NCNTs) for the oxygen reduction reaction (ORR) in alkaline media has been developed. The as prepared material (NCNTs-AgNFs) has been characterized by various instrumental methods. The morphological analysis shows the unique rose-like AgNFs are placed onto the NCNTs with better dispersion. The higher population of AgNFs has also been observed onto NCNTs coated glassy carbon (GC) rather than bare GC plate. The X-ray photoelectron spectroscopy shows chemical reduction and N-doping has done successfully with the restoring sp 2 domain in carbon network. The electrocatalytic activities have been verified using cyclic voltammetry (CV) and hydrodynamic voltammetry techniques in 0.1 M KOH electrolyte. The resulting catalyst system, NCNT-AgNFs, surpasses the performance of Pt/C, in terms of a kinetic current density, better fuel selectivity and durability. It is also noteworthy that the NCNT-AgNFs exhibits a four-electron reduction pathway for ORR with lowering H2 O2 yield. The admirable performance of NCNT-AgNFs catalyst along with higher durability holds great potential for application in various fuel cells as cathode catalyst. Graphical abstract: Highlights: Nonprecious metal silver has been used as cathode catalyst instead of Pt in fuel cell. Rose like silver nanoflowers have been synthesized on nitrogen doped CNT. Around four electron-transfer and less H2 O2 can be obtained by using this catalyst. This catalyst shows better anodic fuel tolerance. Long term stable than the commercial Pt/C.